Minimum effective volume of 0.2% ropivacaine for ultrasound-guided axillary brachial plexus block in preschool-age children - Liang Chen (Nature Portfolio, 2021)
Abstract Ultrasound-guided axillary brachial plexus block is increasingly used in preschool-age patients. However, the minimum effective volume of local anaesthetics has not been determined. With ethical committee approval and written informed consent from the guardians of all paediatric patients, we studied 27 consecutive patients aged 3 to 6 years who were scheduled for hand surgery. After general anaesthesia, eligible patients received a set volume of ultrasound-guided axillary brachial plexus block. We determined the volume of 0.2% ropivacaine for consecutive patients from the preceding patient’s outcome. The initial volume was 0.4 ml/kg. The testing interval was set at 0.05 ml/kg, and the lowest volume was 0.1 ml/kg. The following conditions were defined as a successful block: no heart rate changes, body movement, or ventilatory disorders during the operation; no use of fentanyl in the PACU; and a postoperative sensory block score < 3. The sequences of positive and negative blocks in consecutive patients were recorded. Using probit regression analysis, the 50% effective volume was 0.185 ml/kg (95% CI 0.123–0.234), and the 95% effective volume was 0.280 ml/kg (95% CI 0.232–0.593). EV50 and EV95 values of 0.2% ropivacaine for ultrasound-guided axillary brachial plexus block were 0.185 ml/kg and 0.280 ml/kg, respectively.